Posvojitve v Sloveniji kot oblika socialnega starševstva - Klun, Maja (Socialno delo, 2009)
The paper draws attention to the problem of adoptions at the national level. In Slovenia, people facing infertility decide to adopt children when they lose hope of having their own. However, excessively long periods of foster care and long waiting lists (three to five years) result in a big discrepancy between the number of applications registered by the centres of social work. Although adoptions are the oldest form of social parenthood and are legally recognised, research shows thar the responses of the environment to adoptive families are diverse. The adoptive family is viewed as different from the biological one, because adoptive parents do not share the same genetic material with their children. Apart from the usual problems occurring also in the biologically constructed family, adoptive families also face the problems brought about by the specificity of adoption which allows for no predictability of what it will bring, and does not guarantie success. As adoptive families are influenced by the circumstances and the attitudes of people involved in the adoption process, it is important for the adoptive parents to keep educating themselves about the potential problems of adoption.
Keywords: posvojitve; starševstvo; socialno starševstvo; Slovenia; Slovenija